Readiness of healthcare facilities with tuberculosis services to manage diabetes mellitus in Tanzania: A nationwide analysis for evidence-informed policy-making in high burden settings. - Festo K Shayo; Sigfrid Casmir Shayo (PLoS ONE)
Introduction Double disease burden such as Tuberculosis and Diabetes mellitus comorbidity is evident and on rising especially in high burden settings such as Tanzania. There is limited information about the availability of tuberculosis/diabetes integrated healthcare services in Tanzania. Therefore, this study explored the availability and examined the readiness of healthcare facilities with tuberculosis services to manage diabetes mellitus in Tanzania. Methods We abstracted data from the 2014-2015 Tanzania Service Provision Assessment Survey datasets. The service availability was assessed by calculating the proportion of tuberculosis facilities reported to manage diabetes mellitus. There were four domains; each domain with some indicators for calculating the readiness index. High readiness was considered if the tuberculosis facilities scored at least half (≥50%) of the indicators listed in each of the four domains (staff training and guideline, diagnostics, equipment, and medicines) as is recommended by the World Health Organization-Service Availability and Readiness Assessment manual while low readiness for otherwise. Results Out of 341 healthcare facilities with tuberculosis services included in the current study, 238 (70.0%) reported providing management for diabetes mellitus. The majority of the facilities were dispensaries and clinics 48.1%; publicly owned 72.6%; and located in rural 62.6%. Overall, the readiness of tuberculosis facilities to manage diabetes was low (10.8%). Similarly, the readiness was low based on the domain-specific readiness of trained staff and guidelines. Conclusion Although the majority of the healthcare facilities with tuberculosis services had diabetes mellitus services the overall readiness was low. This finding provides a piece of evidence to inform the policymakers in high burden and low resource countries to strengthen the co-management of tuberculosis and diabetes.